A long goodbye. Issue 1 (22nd August 2018) - Hodges, Dawn Z.
Abstract : Many of you regular readers know I retired recently. I had announced my retirement seven months prior to my departure, at the request of the president. She wanted to hire someone in early to have a transition period for the new chief academic officer.